PENTINGNYA PENGGUNAAN BAHASA INDONESIA DI PERGURUAN TINGGI - Gusnayetti Gusnayetti (Ensiklopedia of Journal, 2020)
The Indonesian Ministry of National Education Director General decided to include Indonesian as one of the subjects that must be taught in all tertiary institutions and departments. The aim is to hone language skills and develop students' personalities. It has become an obligation for us as Indonesian Citizens (WNI) to master and apply Indonesian language in everyday life properly and correctly, so that Indonesian language can be maintained its authenticity. The purpose of this study is to find out: 1) understanding of language; 2) Indonesian Language courses for students; 3) The importance of Indonesian in universities; 4) The purpose and benefits of the Indonesian Language course. The conclusions that can be drawn are: Indonesian is important to be studied in higher education, because Indonesian is a unifying language, because in universities every student comes from various regions in Indonesia. Then, Indonesian as a guide for the preparation and use of good and correct grammar in scientific communication (thesis, thesis, dissertation, etc.), besides studying Indonesian for students at the university as well as studying Indonesian subjects in high school, however discussion at the university is more specific and in-depth, and most students still want to learn Indonesian because in order for them to speak the language properly and correctly, Indonesian is also important to be preserved by native speakers. Suggestions that can be given are: that the Indonesian language needs to be learned, because in this way we also indirectly have preserved our language. Who else will preserve this Indonesian language if we are not Indonesian citizens themselves. that the Indonesian language needs to be learned, because in this way we also indirectly have preserved our language. Who else will preserve this Indonesian language if we are not Indonesian citizens themselves.